Beam Squint Effects of Quantum based Carbon Nanotube Antenna Array for Optical Communication Systems - Muhanad M. Jameel; Jawad A. Hassan (Iraqi Journal of Laser, 2025)
This work examines the beam squint effects of quantum-based carbon nanotube (CNT) antenna arrays for optical plasmonic communication systems functioning within the 300 THz to 700 THz frequency spectrum. The distinctive quantum confinement characteristics of carbon nanotubes (CNTs), together with surface plasmon polariton (SPP) interactions, result in notable frequency-dependent phase shifts, causing beam squint errors in phased array systems. Simulation findings indicate that at 300 THz, a CNT array with an inter-element spacing of λ/2 (500 nm) has a beam squint of 0.2° per 100 THz bandwidth. As the frequency ascends to 700 THz, the beam squint effect amplifies, reaching 0.8° per 100 THz as a result of heightened plasmonic dispersion and quantum-induced phase shifts. The group delay variation throughout the bandwidth is measured at 12.4 fs at 300 THz and 5.6 fs at 700 THz, affirming the nonlinear characteristics of quantum plasmonic wave propagation. The results underscore the significant influence of beam squint in nanoscale optical phased arrays and provide a basis for the creation of adjustable CNT-based plasmonic antennas for advanced optical communication systems.